1989
DOI: 10.1128/mcb.9.11.5105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that xeroderma pigmentosum cells from complementation group E are deficient in a homolog of yeast photolyase.

Abstract: Xeroderma pigmentosum (XP) patients are deficient in the excision repair of damaged DNA. Recognition of the DNA lesion appears to involve a nuclear factor that is defective in complementation group E (XPE binding factor). We have now identified a factor in the yeast Saccharomyces cerevisiae that shares many properties with XPE binding factor, including cellular location, abundance, magnesium dependence, and relative affinities for multiple forms of damaged DNA. Yeast binding activity is dependent on photolyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…There is a rough correlation between the level of UVDRP and nucleotide excision repair [8]. Furthermore, it has been demonstrated that nuclear extracts isolated from some mammalian and yeast repair mutants fail to interact with damaged DNA [3,9,10]. These results strongly suggest the important role of cellular DRP in assisting in DNA repair.…”
Section: Introductionmentioning
confidence: 49%
See 3 more Smart Citations
“…There is a rough correlation between the level of UVDRP and nucleotide excision repair [8]. Furthermore, it has been demonstrated that nuclear extracts isolated from some mammalian and yeast repair mutants fail to interact with damaged DNA [3,9,10]. These results strongly suggest the important role of cellular DRP in assisting in DNA repair.…”
Section: Introductionmentioning
confidence: 49%
“…The amount of WDRP from yeast and HeLa crude nuclear extracts is 0.55 and 0.077 molecules per megabase of genomic DNA, respectively. The human UVDRP binding increased by at least 30-fold using nuclear extracts partially purified from the HA column (data not shown), which resulted in an estimated value of more than 2.2 molecules per megabase reported by Patterson and Chu [9]. The yeast UVDRP from crude nuclear extracts is about 0.55 molecules per megabase of genomic DNA.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…XPE interacts with DDB-2, a 178kDa protein, to form the UV-DDB damage recognition complex that stimulates the damage recognition step in GG-NER. 16 XPE interacts with a variety of proteins to modulate cellular responses to DNA damage. Interactions between XPE and the CBP/p300 17,18 and STAGA 18,19 chromatin remodeling complexes also are critical for the efficient removal of damage by the GG-NER pathway.…”
Section: Finding Dna Damage: Xpa Xpc and Xpementioning
confidence: 99%